2015
DOI: 10.1016/j.ijheatmasstransfer.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of heat pipe-assisted latent heat thermal energy storage with simultaneous charging and discharging

Abstract: Melting and solidification of a phase change material (PCM) held within a vertical cylindrical enclosure that is integrated with a heat pipe (HP) is simulated as a single module. The HP is heated from the bottom to melt (charge) the PCM that is positioned in the middle of the HP length, and is cooled from the top to solidify (discharge) the PCM. Three modes of operation are considered in this study (i) charging-only, (ii) simultaneous charging and discharging, and (iii) discharging-only. All modes of operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The authors concluded that PCM-HPHX systems with a smaller HP-HP spacing have smaller temperature drops and higher exergy efficiencies. An alternative PCM-HPHX design for integration with Dish-Stirling systems was studied by Sharifi et al [71] in which a single HP was used for both charging and discharging of the PCM. In a related study, Cui et al [72] considered a HP receiver in which a HP directly receives solar irradiation and transfers it to a PCM and external fluid flow.…”
Section: Solar Thermal Power Generationmentioning
confidence: 99%
“…The authors concluded that PCM-HPHX systems with a smaller HP-HP spacing have smaller temperature drops and higher exergy efficiencies. An alternative PCM-HPHX design for integration with Dish-Stirling systems was studied by Sharifi et al [71] in which a single HP was used for both charging and discharging of the PCM. In a related study, Cui et al [72] considered a HP receiver in which a HP directly receives solar irradiation and transfers it to a PCM and external fluid flow.…”
Section: Solar Thermal Power Generationmentioning
confidence: 99%
“…Shabgard et al [40] investigated the use of a heat pipe PCM TES system for use in a dish-Stirling system where the PCM acts as a thermal buffer to alleviate transients in solar insolation. Sharifi et al [41] examined a system that had a single heat pipe that was used for both charging and discharging of the PCM for a dish-Stirling receiver. In a system considered by Cui et al [42], a heat pipe is directly irradiated and transfers the energy to the PCM and heater head.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modeling has been used to analyze heat transfer processes both (i) within HPs [22][23][24][25][26][27][28][29][30][31][32] and (ii) external to HPs such as those equipped with exterior fin arrays [19][20][21][22]. Both approaches have employed simplifying assumptions.…”
Section: Introductionmentioning
confidence: 99%